ANALISIS PENGARUH LIKUIDITAS, WAKTU JATUH TEMPO DAN KUPON OBLIGASI TERHADAP PERUBAHAN HARGA OBLIGASI KORPORASI DI BURSA EFEK INDONESIA - Subagia, I Ketut; Sedana, Ida Bagus Panji (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of liquidity, maturity and coupon bonds to changes in prices corporate bonds. This research was conducted at the companies which issuing corporate bonds in the Indonesia Stock Exchange in the first quarter of 2013 until the second quarter of 2014. The samples used in this study were 54 corporate bonds. Based on the results of the analysis found that liquidity significant and positive impact on price changes corporate bonds first quarter of 2013 until the second quarter of 2014. Maturity significant and positively related on price changes corporate bonds first quarter of 2013 until the second quarter of 2014. Coupon not significant and not positively influence on price changes corporate bonds first quarter of 2013 until the second quarter of 2014. Keywords: liquidity, maturity, coupon, bond prices